Law on Urology Specialists in Providing Kidney Transplantation Service - Prisnamurti, Fitra Hardian; Panji, Bambang; Romadhon, Ahmad Heru (Journal of Law, Politic and Humanities, 2025)
Kidney transplantation is a crucial healthcare service in managing end-stage chronic kidney disease. Despite its significant benefits for patients' survival and quality of life, this medical procedure may raise legal issues, particularly regarding the illegal trade of human organs. This study aims to analyze the legal basis, authority, and legal protection for urologist specialists in delivering kidney transplant services in Indonesia. The method employed is normative legal research with statutory and conceptual approaches. The findings indicate that kidney transplantation is permitted as long as it is conducted for humanitarian purposes, free from commercialization, and in accordance with positive law, such as the Health Law No. 17 of 2023 and Government Regulation No. 53 of 2021. Furthermore, urologist specialists must meet professional competency standards and operate within their authorized scope of practice. Legal protection is essential to ensure legal certainty in medical practice. From both Islamic and Catholic religious perspectives, kidney transplantation is allowed if performed voluntarily and ethically to help others.